The Influence of Return on Asset, Corporate Social Responsibility, To Company Value (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine how partially and simultaneously the Return on Asset and Corporate Social Responsibility influence the value of companies in manufacturing listed on the Indonesia Stock Exchange for the period 2016-2018. Factors tested in this research are return on assets and corporate social responsibility as independent variables, while company value as a dependent variable. The research method is the descriptive method. The population in this study is a manufacturing company listed on the Indonesia Stock Exchange for the period 2016-2018, which totals to 154 companies. The technique of sample used in this research is non-probability sampling with the purposive sampling method, so the number of samples is 85. In addition, the data analysis used in this study is multiple linear regression analysis at a significance level of 5%. The program used in analyzing data using Eviews 10. The results showed that partially and simultaneously the return on assets and corporate social responsibility affect the value of the company. In addition, the research results also show that the magnitude of the influence of return on assets and corporate social responsibility in contributing influence on the value of the company is 48.5%.